Multipoint left ventricular pacing effects on hemodynamic parameters and functional status: HUMVEE single-arm clinical trial (NCT03189368) - Christos-Konstantinos Antoniou; Polychronis Dilaveris; Christina Chrysohoou; Konstantinos Konstantinou; Nikolaos Magkas; Panagiotis Xydis; Panagiota Manolakou; Ioannis Skiadas; Konstantinos A. Gatzoulis; Dimitris Tousoulis; Costas Tsioufis (Hellenic Journal of Cardiology, 2022)
Objectives: The aim of this study was to assess the capacity of optimized multipoint pacing (MPP) over optimized cardiac resynchronization therapy (CRT), in terms of clinical, functional, and echocardiographic parameters among patients with dyssynchronous heart failure (HF). Methods: Eighty patients (Caucasian, 77.5% male, 68.4 ± 10.1 years, and 53.8% ischemic cardiomyopathy) sequentially received optimized CRT and optimized MPP over 6- and 12-month periods in a single-arm clinical trial. Clinical, laboratory, and echocardiographic assessment was conducted at baseline and after the completion of each step. Results: Significant additive effects of optimized MPP over optimized CRT were noted with regard to 6-min walking distance (baseline/optCRT/optMPP: 293 ± 120 m vs 367 ± 94 m vs 405 ± 129 m and p < 0.001), NYHA class (2.36 vs 2.19 vs 1.45 and p < 0.001), VTIlvot (14.25 ± 3.2 cm vs 16.2 ± 4 cm vs 17.5 ± 3.4 cm and p < 0.001), stroke volume (48 ± 13.5 ml vs 55 ± 15 ml vs 59 ± 15 ml and p < 0.001), left ventricular ejection fraction (LVEF) (29% ± 7.1% vs 33% ± 7.3% vs 37% ± 7.7% and p < 0.001), maximal left atrial volume (77.2 ± 34.2 ml vs 74.2 ± 39.5 ml vs 67.7 ± 32 ml and p = 0.02), pulmonary artery systolic pressure (35.9 mmHg vs 33.5 mmHg vs 31 mmHg and p < 0.001), and right ventricular strain (−8.3% ± 6.9% vs −8.8% ± 6.6% vs −11.8% ± 6.1% and p = 0.022). With regard to VAC, stroke work (SW), and CP as percentages of maximal, there was a significant difference detected as compared to baseline for both CRT and MPP. Additive effects persisted only if suitable MPP dipoles were present. Exploratory analysis revealed that ischemic cardiomyopathy continued to exhibit significant differences that favor MPP, whereas nonischemic cardiomyopathy had similar findings with regard to total left atrial strain and quality of life. Conclusions: Optimized MPP showed significant improvements in hemodynamic parameters and ventricular function in patients with HF over optimized CRT. The beneficial effect was more prominent in men and in those with rather reduced LVEF, consistent with findings that suggest a beneficial trend in VAC and CP with more homogeneous depolarization offered by optimized MPP.